ANALISIS PEMASARAN LADA PUTIH (Piper Nigrum) DI KECAMATAN SIMPANG PESAK KABUPATEN BELITUNG TIMUR - Hieldaria Whardani; Ignatius Suprih Sudrajat; Susi Widiatmi (Fakultas Pertanian UST, 2019)
This study aims to determine the marketing channels of white pepper, the factors that influence the marketing margins of white pepper in the sub-district of Simpang Pesak, East Belitung Regency. This research was conducted in the intersection of the East Belitung district, involving 30 white pepper farmers, as well as following the marketing flow, namely traders, wholesalers and retailers. The data analysis method used in this study is descriptive analysis, using multiple linear regression analysis. The results of the study show that there are 2 marketing channels in the sub-district intersection that are Channel I farmers - traders, wholesalers - retailers, channel II farmers - big traders - retailers. Hypothesis testing used is the test of determination, F test and t test. The test value of determination on marketing margins is 0.931 or 93%, which means that the independent variables in the study provide all the information needed by the marketing margin (significant effect). The F Test Value on the marketing margin, namely the four independent variables have a significant effect on the marketing margin. The results of the t-test analysis show that there are two variables that have a significant effect on marketing margins, namely the price at the farmer level and the number of marketing institutions, while those that have no significant effect are the variable sales volume and marketing costs.